Dimensionamento da população de cães e gatos domiciliados e semidomiciliados da cidade de Guarapuava-PR - Riffert, Renata Diniewicz (2020)
The objective of this work was to measure the canine and feline population domiciled and semi-domiciled in the city of Guarapuava, Paraná, Brazil. In total, 695 interviews were carried out in residences distributed in the 20 neighborhoods of the municipality. The sample size was calculated considering the total number of residences, 44,497, with a 95% confidence interval and standard error of 20%. The dog:human ratio found in the municipality was 1:1.77. This number ranged from 1.06 to 2.92 among neighborhoods. The cat:human ratio was 1:5.98. Considering the current city population, the number of dogs domiciled is 102,544 and of cats is 30,351; being 24,098 dogs and 17,088 cats semi-domiciled. The dog estimation is above the one established by the WHO, which is from 1:7 to 1:10 (dog:human). It is necessary to implement public policies that enable the development of an efficient population control program for dogs and cats, such as shared responsibility through actions that involve the population, public agencies, companies, universities and NGOs, in addition to the introduction of responsible ownership education in schools and accountability of tutors.